(untitled) (Fiep Bulletin - online, 2013)
The injury of anterior cruciate ligament (ACL) promotes instability to articulate generating biomechanic alterations in the gait standard. The objective of this study was the identification of the angular and space-temporal parameters of the joints of the lower member during the gait in different periods after-reconstruction of the ACL. Four volunteers of the masculine sex had participated of the study, being collected in the periods of 30, 60 and 90 days after-reconstruction of the ligament, the images had been acquired by a digital camera SONY®, being processed in Peak Performance software. The results had shown that didn’t have differences where comparison of the member operated (MO) with the member not operated (MNO) in the angular variable for the three analyzed periods, however in the temporal variable between the period of 60 and 90 days, in the swing of the member not operated (BMNO) and simple support of the operated member (ASMO) had been evidenced differences thus influencing the time of the passed one (TP). Finally, for the space variable significant differences in the periods analyzed in the length of the passed one had not been found (CP), length of the step of the operated member (CPMO) and length of the step of the member not operated (CPMNO). It is presumed that a trend of the patients exists to reduce the contraction of quadríceps, for subconscious adaptations during the floor, in order to prevent the prior of the shinbone in relation to thingborn, being that these still are not inside of a standard considered normal for the march.